Establishing Inclusion for SEN in Faith-based Schools in Thailand: A Case Study - Kimberly R. Japon; Ian C. Abordo (PT ARRUS Intelektual Indonesia, 2024)
In Thailand, research on inclusion program predominantly focused on inclusion programs in government-run schools. The need to understand specific inclusion of students with special needs (SEN) within faith-based settings cannot be neglected. This study addresses this gap by investigating the processes by which diverse faith-based schools in Thailand foster the inclusion of students with special needs. Through in-depth interviews with nine participants and observations from two faith-based schools, a case study was employed, incorporating within-case and cross-case analysis. Findings reveal that faith-based schools established inclusion models aligned to the schools’ mission statements and values. Inclusive practices were open communication, parental involvement, teachers’ collaboration, and specific inclusion strategies such as accommodation and modification, as well as celebrating diversity and inclusion. Barriers to inclusion include lack of knowledge, skills, and training in inclusion. Further research on the long-term influence of faith-based schools’ values on inclusion practices and the quality of life of SEN can enhance global understanding of faith-based approaches to inclusivity.